2007
DOI: 10.1167/iovs.07-0156
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of VEGF in Murine Retina via Monocyte Recruitment after Retinal Scatter Laser Photocoagulation

Abstract: Retinal scatter laser photocoagulation induced upregulation of VEGF in the sensory retina and RPE-choroid at an early period. The authors speculate that the major source of VEGF in the retina after retinal scatter laser photocoagulation is the recruited monocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 30 publications
3
54
0
2
Order By: Relevance
“…Furthermore, several studies have suggested that the expression of various chemokines can be regulated by complement activation products, including MAC (39 -42). It is also known that various chemokines can modulate the levels of growth factors (43)(44)(45)(46). However, the link between MAC, chemokines, and growth factors in laser-induced CNV is not elucidated thus far.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several studies have suggested that the expression of various chemokines can be regulated by complement activation products, including MAC (39 -42). It is also known that various chemokines can modulate the levels of growth factors (43)(44)(45)(46). However, the link between MAC, chemokines, and growth factors in laser-induced CNV is not elucidated thus far.…”
Section: Discussionmentioning
confidence: 99%
“…17,19,20,23 The RPE/ choroid complex was carefully isolated from the eyes at 3 days after photocoagulation and sonicated in lysis buffer (20 mM imidazole HCl, 10 mM KCl, 1 mM MgCl 2 , 10 mM EGTA, 1% Triton X-100, 10 mM NaF, 1 mM Na molybdate, 1 mM EDTA, protease inhibitor cocktail [SigmaAldrich, St. Louis, MO]) on ice for 15 minutes. The lysate was centrifuged at 15,000 rpm for 15 minutes at 48C, and the VEGF protein levels in the supernatants were determined using a Quantikine M ELISA kit (threshold of detection, 3 pg/mL; R&D Systems, Minneapolis, MN) that recognizes all splice variants at wavelengths of 450 to 570 nm (SpectraMax340; Molecular Devices, Sunnyvale, CA).…”
Section: Elisa For Vegfmentioning
confidence: 99%
“…Laser photocoagulation has been shown to increase the expression of VEGF and transcription factors by cultured human retinal pigment epithelial cells, with upregulation of VEGF occurring from 6 to 72 h [28]. In contrast, Itaya et al [29] reported that the maximum VEGF level was detected on day 3 after photocoagulation in vivo, coinciding with the peak of macrophage infiltration. Furthermore, changes in VEGF mRNA expression were confined to retinal pigment epithelial cells in miniature pigs after laser photocoagulation, with a decrease in expression immediately after photocoagulation and a return to baseline by 42 days [30].…”
Section: Discussionmentioning
confidence: 99%